Al-Maslahah Al-Mursalah dalam Penentuan Hukum Islam - Hendri Hermawan Adinugraha; Mashudi Mashudi (Jurnal Ilmiah Ekonomi Islam, 2018)
The beginning of the problem in the development of Islamic law was coincided after the death of Prophet Muhammad SAW. The legal issues that emerge along with the advancement of the times and the development of technology and social change continue to emerge as the dynamics of human life “current era” in this world. The verses of the Qur’an and the hadiths of the Prophet are required to be able to solve the problems of the ummah. The existence of al-maslahah al-mursalah is a formulation of contemporary ijtihad in establishing Islamic law by keeping referring to the two sources of law namely Alqur’an and al-hadist, in order to find answers of various problems that arise in the midst of the ummah. The purpose of this study is to find out and analyze the relevance of al-maslahah al-mursalah with the context of current matters as the determination of Islamic law. The method of analysis in this qualitative research uses literature approach by reading some works on al-maslahah al-mursalah in the determination of Islamic law. The results of the study and the analysis of this study show that al-maslahah al-mursalah can only be a legal determination on mu’amalah affairs, it has been agreed by jumhurul ‘ulama. The legal product established by the al-maslahah al-mursalah method was considered to be more effective and flexible in dealing with and answering contemporary mu’amalah issues that have not clearly stated its legal provisions in the texts, without violating the rules of the Qur’an and hadith. The purpose of al-maslahah al-mursalah is to optimize the maintenance of the benefit of mankind, because it is a reflection of the manifestations of the concept of hifzu ad-din, an-nafs, al-’aql, an-nasl, and al-mal (al-’aradh).Saran sitasi:  Adinugraha, H., & Mashudi, M. (2018). Al-Maslahah Al-Mursalah dalam Penentuan Hukum Islam. Jurnal Ilmiah Ekonomi Islam, 4(01), 63-75. doi:http://dx.doi.org/10.29040/jiei.v4i1.140